2014
DOI: 10.1002/joc.4129
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal intercomparison of observational rainfall datasets over India during the southwest monsoon season

Abstract: The Indian monsoon is an important component of Earth's climate system, accurate forecasting of its mean rainfall being essential for regional food and water security. Accurate measurement of rainfall is essential for various water-related applications, the evaluation of numerical models and detection and attribution of trends, but a variety of different gridded rainfall datasets are available for these purposes. In this study, six gridded rainfall datasets are compared against the India Meteorological Departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 24 publications
5
88
0
Order By: Relevance
“…Figure 9 shows the decadal trends of extreme rainfall (i.e., 95th percentile precipitation for JJA) in the datasets over the period 1998-2007 calculated through a linear regression coefficient. Except for APHRODITE, ERA-Interim, and JRA55, the rest shows a remarkable increasing trend over central India, which is consistent with the finding of Rana et al (2015) and Prakash et al (2014). Singh et al (2013) found that APHRODITE has opposite trend signs for extreme precipitation intensity from the 2000s onwards when compared with the IMD dataset (2140 rain-gauge station).…”
Section: Interannual Variabilitysupporting
confidence: 82%
“…Figure 9 shows the decadal trends of extreme rainfall (i.e., 95th percentile precipitation for JJA) in the datasets over the period 1998-2007 calculated through a linear regression coefficient. Except for APHRODITE, ERA-Interim, and JRA55, the rest shows a remarkable increasing trend over central India, which is consistent with the finding of Rana et al (2015) and Prakash et al (2014). Singh et al (2013) found that APHRODITE has opposite trend signs for extreme precipitation intensity from the 2000s onwards when compared with the IMD dataset (2140 rain-gauge station).…”
Section: Interannual Variabilitysupporting
confidence: 82%
“…These may suggest that all of these data sets are affected by some common factors in determining the characteristics of these data sets. For example, the station data sets included in each analysis data set may provide high consistency in the spatial distribution pattern, but different analysis schemes may lead to a larger spread in the magnitude of their variability because of different basis functions employed in different interpolation schemes (e.g., Xie and Arkin, 1995;Prakash et al, 2014). This is just a hypothesis and needs close examination in future studies.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…These new data sets also introduce uncertainties in calculating regional climate characteristics because of the differences amongst them. Based on these concerns, two recent studies by Prakash et al (2014) and Kim et al (2015) examined uncertainty in calculating precipitation climatology over India and its surrounding regions using multiple precipitation analysis data sets. These two studies have revealed independently that there exist substantial amounts of differences amongst today's gridded precipitation data sets resulting in uncertainties in the calculated precipitation climatology and that the uncertainty and the spread amongst multiple data sets vary according to regions as well as seasons.…”
Section: Introductionmentioning
confidence: 99%
“…Spatial analyses created from interpolating station data [48,49] provide coarse scale climate trends [2,42], but in areas such as Mongolia, there are few meteorological stations [4]. Historically, areas with sparse populations have greater distances between stations [1,43] due to the lack of people and funding needed to perform the manual observations.…”
Section: Data Considerationsmentioning
confidence: 99%
“…[43], have a monthly time scale [48] that cannot be used to estimate details such as changes in the precipitation phase [55], providing an impetus for making spatial estimates of uncertainty in climate trends using herder observations ( Figure 5 and Table 2). Thus, in a data sparse region like Mongolia, herder observations can help in the assessment of climate change at a finer resolution ( Figure 5 and Table 2).…”
Section: Data Considerationsmentioning
confidence: 99%